V.M. Golitsyn and A.M. Gorky: The History of Board Games - Elena V. Kudrina (Литературный факт, 2023)
The article deals with newly founded letter from Vladimir Mikhailovich Golitsyn to Maxim Gorky from the section of children’s letters of A.M. Gorky Archive (IWL RAS). The letter was written on June 8, 1935 and was dedicated to historical games for Soviet children. It contains an approximate plan for a series of board games that were developed by V.M. Golitsyn. Historical games were not just entertainment and a pleasant pastime for Golitsyn, but an important element of teaching and raising children. Their goal was to arouse the interest of players in history, geography, literature, immersion in an interesting and exciting world of knowledge and adventure, the development of attention and memory. In the letter, Golitsyn expresses doubts and asks Gorky for advice. This letter was unknown to researchers of the artist and inventor. The article clarifies the history of Golitsyn’s strategic games “Pirates,” “Capture of Colonies,” “Rescue of Chelyuskinites,” “Runaways,” etc. The board game “Pirates” was approved by Gorky, it was played by A.A. Zhdanov, V.M. Molotov and L.M. Kaganovich, but because of bureaucratic and ideological obstacles, it was not published in a separate edition during the author’s lifetime, and most Soviet children did not know about this educational game. V.M. Golitsyn’s letter to Gorky and its appendix are published for the first time.